Enhanced nucleate boiling on 3D-printed micro-porous structured surface. (August 2018) - Bian, Haozhi; Kurwitz, C.; Sun, Zhongning; Cheng, Kun; Chen, Kailun
Abstract: With the fast growth of 3D printing technologies, it is promising to apply 3D printed structures to nuclear power plant (NPP) devices for heat transfer enhancement. Since Inconel and steel are commonly used materials for NPP devices (e.g. reactor core components and steam generators), investigations on 3D printed structures made of these materials are of necessary. In the present work, an Inconel smooth plate and three 3D-printed test samples (grooves, pin-fins and cubes) with micro-porous structured surfaces were tested. The smooth plate is made of Inconel and the 3D printed samples are made of steel-bronze mixture. In tests, heat flux, surface temperature, pressure, etc. were obtained by a data acquisition system. In addition, videos were recorded by a NAC high speed camera for visualization study. Comparisons were made among various testing samples to find the optimum structure. Results indicate that all the 3D printed samples show better boiling heat transfer at low heat flux conditions compared to that of the Inconel plate. With the increase of heat flux, the degree of heat transfer enhancement weakens. Among the three 3D printed samples, the cubes sample demonstrates the best heat transfer performance and the pin-fins one shows the worst.